Effect of Solanum nigrum L. on blood glucose concentration and lipid profile in normal and STZ-induced diabetic rats - KB, Ahir; BG, Patel; SB, Patel; FA, Mehta (Pharmacognosy Communications)
Background: Fruits of Solanum nigrum L. (Solanaceae) are used in traditional medicine for a number of ailments including metabolic disorders. Objectives: The ethanolic extract of fruits of Solanum nigrum L. (SNE) was investigated to evaluate the effects of on blood glucose concentration, lipid profile and renal function tests and their possible mechanism of action involved in these activities. Materials and Methods: SNE (100 and 250 mg/kg; p.o.) was administered to diabetic rats and the standard drug Insulin (5 I.U. /kg; i.p.) to a group serving as positive control. Effects of SNE on various biochemical parameters were studied in diabetic rats. Results: Oral administration of SNE (100 and 250 mg/kg.) for 21 days to streptozotocin-induced diabetes rats significantly (p<0.05) decreased the levels of blood glucose and improved the levels of plasma insulin. The levels of triglycerides, cholesterol, high density lipoprotein (HDL), low density lipoprotein (LDL), very low density lipoprotein (VLDL), aspartate amino transferase (AST) and alanine amino transferase (ALT), urea and creatinine, were markedly altered in STZ-induced diabetic rats. Oral administration of SNE restored all these biochemical parameters to near control levels. Discussion and Conclusions: The present study reveals the efficacy of Solanum nigrum fruit extract in the amelioration of diabetes and its associated complications. The anti-diabetic and anti-hyperlipidemic effect of Solanum nigrum was also compared with insulin, a standard drug.
Keywords: Solanum nigrum; diabetes mellitus; blood glucose; lipidprofile; nephroprotection; streptozotocin